THE EFFECT OF FERRULE LENGTH ON FRACTURE RESISTANCE OF TEETH RESTORED WITH TWO DIFFERENT POSTS CEMENTED WITH TWO TYPES OF LUTING MATERIALS. - 1-Mansour Mahdi AlYami, 2-Mohammed ShaghathHadiAlsaqour, 3-Ali Saeed Ali Alyami, 4-Ali Saleh Mohammed Alkhamsan, 5- Hassan MehsenAlsharief (Chelonian Research Foundation, 2023)
Objectives: To determine the ferrule length influence on fracture resistance of teeth repaired with two distinct forms of posts, luted using two different cement luting kinds. Materials: Eighty healthy, recently removed, non-caries central maxillary incisors were collected and preserved at room temperature in 0.9% normal saline solution. The teeth were randomly allocated into two equal groups. Based on the cement type utilized in its cementation, each group was further subdivided into two subgroups: composite resin and zinc phosphate. The compressive force was applied at a crosshead speed of 0.5 mm/min using universal testing equipment until all samples were fractured. Results: Resin cementation of the cast post exhibited greater load values than the resin phosphate cementation of the cast post with and without the ferrule effect. However, increasing the ferrule length with the two types of cement used for cementing various posts in their respective root canals enhanced the fraction resistance. Conclusion: Root-filled teeth revealed an enhanced resistance to fracture with increasing the Ferrule length. Root-filled teeth that underwent restoration by flexi post and cementation using composite resin had a higher fracture resistance than cementation with zinc phosphate. Root-filled teeth that underwent restoration with cast post and cementation with composite resin had a greater resistance to fracture in comparison with the cast post cemented by zinc phosphate. Restoration of Root-filled teeth using flexi post and Ti core had a greater fracture resistance than cast post and its core. Keywords: Fracture Resistance; Central Incisors; Ferrule Length